Development Budget in Bangladesh: Spatial Analysis of Regional Dynamics - Jobaid, Mamnunnah; Khan, Adil Mohammed (Journal of Bangladesh Institute of Planners, 2018)
Regional difference in economic development is a common phenomenon in the developed as well as developing countries as economic development never progresses at the same pace in all the regions of a country. However, the vision of balanced regional growth must be addressed by any government as it ensures equity in development. Bangladesh is a developing country which achieved its independence in 1971. Article 19(2) of the constitution of the Peoples’ Republic of Bangladesh states: “The state shall adopt effective measures to remove social and economic inequality between man and man and to ensure the equitable distribution of wealth among citizens, and of opportunities in order to attain a uniform level of economic development throughout the republic.” In spite of the constitutional obligations, regional variations have been taking place in the development of Bangladesh since the independence. As a result, variations in socio-economic development among regions in Bangladesh have been visible. In this regard, this paper explores the spatial variations in distribution of national budget among various divisions and districts. It analyzes the regional variations of distribution of development budget in the form of Annual Development Plan (ADP) during the period 2012-13 to 2016-17 across various regions in Bangladesh. In this research, Location Quotient (LQ) Method and Gini Coefficient Method have been used to analyze the regional variations of budget distribution to measure the regional disparity of development in Bangladesh. The findings of this research may help the policy makers understand that a more balanced development approach is required in the future to offset the regional variations in development. JBIP, Vol. 11, 2018 (Printed in June 2020), pp. 39-54